What is Success? The Role of Perceived Cultural Tightness in the Clarity of Success Markers - AU, Evelyn Wing-Mun (Institutional Knowledge at Singapore Management University, 2010)
The extent to which norms are clear differ across cultures, as does the extent to which individuals believe that they will be punished for deviating from these norms. In tight cultures, individuals perceive norms to be clear and punishment for deviance to be inevitable. In loose cultures, individuals consider norms to be vague and adherence to them to be flexible. Having clear markers of success provides well-defined standards for people to evaluate others on adherence to the culture’s valued norms. This research examined how people’s perceptions of their culture’s tightness/looseness would relate to their perceptions of markers of success. We predicted that people who viewed their culture as being tight would perceive clearer markers of success in the culture. Furthermore, we examined perceived motivation for success (intrinsic versus extrinsic) as a mediator of the expected link between tightness/looseness and clarity of success markers. Results provide supporting evidence for this prediction. Implications and future directions will be discussed.